PAJAK E-COMMERCE DI KABUPATEN SUMENEP: APA KATA MEREKA? - Faisol, Moh.; Rofiqi, Imam (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
Taxes were the main state of income that used as a tool to finance government activities. One of the means to increase revenue in this state is tax sector, DJP imposes taxes on electronic transactions (e-commerce). The problems from this situation of PMK have maked traders or service providers and marketplace platform providers have to cut taxes (PPN and PPnBM) on each transaction, thus making the transactions complicated, in fact the selling value of goods will be of high value with the imposition of the taxes. This qualitative research was conducted in Sumenep Regency by interviewing 13 informants; 1 academician and 12 business people and e-commerce users. The results of the interview our analyzed, the starting from data reduction, data presentation, and drawing conclusions that assisted by analysis tools of NVivo 12. The results of this research are (1) some taxpayers do not know PMK 210 regarding e-commerce tax. That matter because they have not gotten socialization and are not willing to seek information related the regulations; and (2) the existence of the e-commerce tax consider to be valid. Because taxes payment to the state will return to community, like as a infrastructure, and the other determined by laws and regulations.